The doing business ranking and the design of public policies: the effect of regional dynamics. Issue 1 (1st January 2021) - Estevão, João; Lopes, José Dias; Penela, Daniela
Abstract: The challenge of creating a favourable business environment has motivated academics, international institutions and policy makers. An initiative that has recently been established to facilitate this path has involved the creation of ordered lists that classify the environment around companies and the ease of doing business. The World Bank's DB measure is one such ranking system. This type of ranking has supported much research and many political decision-making processes. However, it is not common in these analyses to consider regional dynamics and how the results of such rankings and investigations should be interpreted considering regional specificities. The objective of this study is to evaluate the business environment and the production of wealth while considering the impacts of these regional dynamics. In particular, we study whether the DB sub-indicators are equally important regardless of a region's level of economic development. The results are clear with evident configurations of dominant sub-indicators that are distinct in three regions. Our results show us that these rankings, and the design of public policies based on them, should consider regional specificities, thus refuting the idea that the design of public policies to improve the framework for companies should follow a "one fits all" intervention model.